Evaluation of the Effects of Low Level Laser Therapy on the Healing Process After Skin Graft Surgery in Burned Patients (A Randomized Clinical Trial) - Kazemikhoo, Nooshafarin; Vaghardoost, Reza; Dahmardehei, Mostafa; Mokmeli, Soheila; Momeni, Mahnoush; Nilforoushzadeh, Mohammad Ali; Ansari, Fereshteh; Razzaghi, Mohammad Reza; Razzaghi, Zahra; Amirkhani, Mohammad Amir; et al. (Journal of Lasers in Medical Sciences, 2018)
Background: Skin graft is standard therapeutic technique in patients with deep ulcers but as every surgical procedure has complications. Although several modern dressings are available to enhance comfort of donor site, using techniques that accelerate wound healing may enhance patient’s satisfaction. Low Level Laser Therapy (LLLT) has been used in several medical fields, especially for wound healing but for treating large ulcers, it may last several months to heal completely. Materials and Methods: The protocols and informed consent were reviewed according to Medical Ethics Board of Shahid Beheshti University of Medical Sciences (IR.SBMU.REC.1394.363) and Iranian Registry of Clinical Trials (IRCT2016020226069N2). Nine patients with bilateral similar grade 3 burn ulcer in both hands or both feet, candidate for Split Thickness Skin Graft (STSG) were selected. One side was selected for laser irradiation and the other side as control, randomly. Laser area was irradiated by red, 655 nm laser light, 150 mW, 2 J/Cm2 for the bed of the ulcer and infra red 808 nm laser light, 200 mW for the margins, every day for 7 days. Results: The rate of wound dehiscence after skin graft surgery was significantly lower in laser treated group in comparison to control group which received only classic dressing (P=0.019). Discussion: In the present study for the first time we evaluate the effects of LLLT on the healing process of skin grafted area in burn patients. The results showed LLLT is a safe effective method which improves graft survival and wound healing process and decreases the rate of wound dehiscence in patients with deep burn ulcer.